Immunization against recombinant GnRH-I alters testicular structure in an experimental boar model. Issue 1 (February 2015) - Li, Yunsheng; Liu, Ya; Su, Shiping; Pu, Yong; Zhang, Xiaorong; Fang, Fugui
Summary The aim of this study was to evaluate and to compare testicular tissue in immunized and control boars. Eighteen male piglets, aged 12 weeks, were vaccinated twice intramuscularly with a maltose-binding protein–gonadotropin-releasing hormone I hexamer peptide (MBP-GnRH-I6). Blood samples were taken at 12, 18, 21 and 24 weeks of age. Serum concentrations of testosterone and GnRH-I antibodies were determined by radioimmunoassay. The pigs were sacrificed 6 weeks after the second immunization. Testicular weight and size were recorded and tissue samples were collected for histological examination. The results demonstrated that active immunization against MBP-GnRH-I6 increased serum GnRH-I antibody levels (P < 0.05) and reduced serum concentrations of testosterone (P < 0.05) when compared with controls. Histological studies performed on testicular tissue revealed clear signs of atrophy in the MBP-GnRH-I6 immunized pigs, and a significant reduction (P < 0.05) in paired testes weight and size were seen in the treated boars. Microscopically, the mean diameter of the seminiferous tubules was markedly reduced (P < 0.01). Spermatogonia were visible, as well as few spermatocytes, but no spermatozoa were detected in the seminiferous tubules. Ultramicroscopic analysis of testicular tissue revealed an increase in the thickness of the basement membrane and extensive damage in the cell organelles of the treated animals, including small spermatogonial size, decreased number of mitochondria and endoplasmic reticulum in the primary spermatocyte and spermatid, a shallow hollow for nuclear membranes in Sertoli cells and mitochondrial vacuolation in Leydig cells. We conclude that MBP-GnRH-I6 induces severe atrophy in the testes of immunized boars.